Evaluation of the Effect of Meatal Stenosis on the Urinary Tract by using Ultrasonography - Saeedi, Parisa; Ahmadnia, Hassan; Akhavan Rezayat, Alireza (Urology Journal, 2017)
Purpose: Circumcision is one of the oldest surgical procedures that originated for religious purposes. Circumcision in infancy is a common procedure in our country and secondary meatal stenosis due to circumcision is a common complication. The aim of our study is to determine the effect of meatal stenosis on the lower and upper urinary tract of circumcised boys by using ultrasonography. Materials and Methods: In this cross-sectional study, we enrolled 87 circumcised boys between 4 to 8 years old with severe meatal stenosis. Clinical findings of our subjects were gathered by a checklist that included: thin stream of urine, upward urine stream deviation, infrequent voiding, urinary tract infections, voiding dysfunction, and urge incontinency. In lab data analysis, complete blood cell count (CBC), urine analysis, urine culture, blood urea nitrogen (BUN), and plasma creatinine level were evaluated. Ultrasonography detected hydronephrosis, hydroureter, bladder wall thickening in a full and empty bladder, bladder volume, and residual urine volume. Result: Narrowing of urine stream is commonly seen (about 54%) among patients with severe meatal stenosis, and similarly in sonographic evaluations the most common symptoms among patients was thickening of the bladder wall that increased in an empty and a full bladder (about 82%). Conclusion: The author of this study recommends performing long-term follow up after circumcision and ultrasonography to detect meatal stenosis before permanent renal damage occurs.